Spectroscopic techniques in the investigation of extraordinary medieval Polish coins: Revealing the presence of hidden cores - Trela Krystian; Gójska Aneta Maria; Miśta-Jakubowska Ewelina A.; Kelemen Mitja; Šmit Žiga; Kędzierski Adam; Garbacz-Klempka Aldona (Nukleonika)
Cross denars, frequently found in Polish hoards, were traditionally thought to be Ag coins with some Cu content. This study investigates the possibility of a hidden Cu core beneath the Ag or Ag–Cu surface of these coins. It raises questions about whether they were counterfeits or intentionally designed for mass production. Unlike Roman denarii, which revealed their cores when broken, the examination of cross denars without damage is challenging. Optical microscopy and microanalysis revealed differences in the composition of early medieval Polish coins, challenging the belief that cross denars were homogeneous Ag–Cu alloys. Detailed spectroscopic analyses, including energy-dispersive X-ray fluorescence (ED-XRF), scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDS), micro X-ray fluorescence (μXRF), and microparticle-induced X-ray emission (μ-PIXE) measurements, were conducted. These analyses of two cross denars uncovered one composed of an Ag–Cu alloy and another manufactured by plating a Cu–Zn core with an Ag sheet. This suggests the need for further research in the history and technology of minting in Poland in the Early Middle Ages. It also prompts a reconsideration of the applicability of noninvasive X-ray techniques for archaeological examinations.